2015
DOI: 10.1002/rrq.110
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Writing Tasks and Students' Analytic Text-Based Writing

Abstract: The Common Core State Standards emphasize students writing analytically in response to texts. Questions remain about the nature of instruction that develops students' text‐based writing skills. In the present study, we examined the role that writing task quality plays in students' mastery of analytic text‐based writing. Text‐based writing tasks (N = 149) were collected from 27 fifth‐grade teachers in an urban district, and teachers completed daily surveys (i.e., instructional logs) to assess the frequency of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…Additionally, cognitively demanding tasks have been shown to be effective for increasing the reading skills of all students—even those with low starting achievement (Newmann, Bryk, & Nagaoka, ; Newmann, Marks, & Gamoran, ). More recently, we found that cognitively demanding writing tasks increase students’ ability to compile evidence and substantively organize their ideas in writing, even after controlling for other dimensions of teachers’ reading and writing instruction (Matsumura, Correnti, & Wang, ). Importantly, this was the only classroom or teacher characteristic to have an effect on students’ analytic thinking.…”
Section: Writing Prompts That Support Analytic Thinking and Reasoningmentioning
confidence: 90%
See 2 more Smart Citations
“…Additionally, cognitively demanding tasks have been shown to be effective for increasing the reading skills of all students—even those with low starting achievement (Newmann, Bryk, & Nagaoka, ; Newmann, Marks, & Gamoran, ). More recently, we found that cognitively demanding writing tasks increase students’ ability to compile evidence and substantively organize their ideas in writing, even after controlling for other dimensions of teachers’ reading and writing instruction (Matsumura, Correnti, & Wang, ). Importantly, this was the only classroom or teacher characteristic to have an effect on students’ analytic thinking.…”
Section: Writing Prompts That Support Analytic Thinking and Reasoningmentioning
confidence: 90%
“…Unfortunately, cognitively demanding writing assignments are rare. Research shows that students mostly do not have the opportunity to write in ways that require higher level thinking (Gilbert & Graham, ; Matsumura et al., ; Newmann et al., ). In our recent study, for example, we found that only a quarter of the writing assignments we collected in fifth‐grade classrooms required deep understanding of a text and had a high level of cognitive demand (Matsumura et al., ).…”
Section: Writing Prompts That Support Analytic Thinking and Reasoningmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have investigated different aspects of analytic text-based writing. Matsumura, Correnti, and Wang (2015) were concerned about the instruction teachers provide in hopes of developing their students' text-based writing skills. Consequently, they investigated the role that writing task quality plays in students' mastery of analytic text-based writing.…”
Section: Analytic Text-based Essay Writingmentioning
confidence: 99%
“…Teachers of upper elementary grades can help students develop higher level thinking skills about texts by regularly assigning writing tasks that provide opportunities to apply this new and challenging skill (Matsumura, Correnti, & Wang, ). Simply assigning such tasks, however, is insufficient.…”
Section: Brief Guide For Providing Written Feedback To Support Studenmentioning
confidence: 99%